Assessment of technical condition of power oil-filled engineering equipment in different operation modes - N. I. Khoroshev (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
Uninterrupted operation and quality of providing consumers with electric energy, safety of productions and their efficiency depend on reliability of equipment and networks functioning. One of the most responsible nodes of power supply systems are power oil-filled electro-engineering equipment of average power. Therefore the paper considers the aspects of assessing technical state of power oil-filled electro-engineering equipment without shutdown on the basis of formalization of keyword diagnostic parameters, characterizing equipment operation. The need of controlling the parameter characterizing the dynamics of thermal wear of transformer isolation on the basis of mathematical integrated function is shown. The authors proposed the assessment mechanism of technical condition of power oil-filled transformers and decision-making support model which are taken as the base for developing the effective service strategy on the current technical state. It was ascertained that application of the approach proposed allows increasing the efficiency of the decisions made in production.